1995
DOI: 10.1007/bf02576802
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin reduces the levels of tumor necrosis factor alpha in a rat model of endotoxemia induced bylipopolysaccharide

Abstract: The role of tumor necrosis factor alpha (TNF) in the toxic and lethal effects of the endotoxemia associated with septic shock is well known. This study was designed to establish whether natural somatostatin (SS-14) is capable of modifying the production of TNF in a model of septic shock induced in the rat by bacterial lipopolysaccharide (LPS), and its theoretical relationship to prostaglandin E2 (PGE2). An experimental study was carried out in 80 Wistar rats subjected to intravenous LPS injection. Perfusion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In our study, we showed that not only TNF‐α, but also IL‐6, Csf2 ( P < 0.001) and IL‐1b ( P = 0.07) protein expression was inhibited by BSCI in maternal plasma after low‐dose systemic LPS administration. Similarly, natural somatostatin (SS‐14) has been shown to be capable of modifying TNF‐α secretion in a rat model of septic shock induced by bacterial LPS . Cortistatin, novel somatostatin‐related cyclic neuropeptide, down‐regulated the production of inflammatory mediators by LPS‐activated macrophages .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we showed that not only TNF‐α, but also IL‐6, Csf2 ( P < 0.001) and IL‐1b ( P = 0.07) protein expression was inhibited by BSCI in maternal plasma after low‐dose systemic LPS administration. Similarly, natural somatostatin (SS‐14) has been shown to be capable of modifying TNF‐α secretion in a rat model of septic shock induced by bacterial LPS . Cortistatin, novel somatostatin‐related cyclic neuropeptide, down‐regulated the production of inflammatory mediators by LPS‐activated macrophages .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, SA13353 further enhanced the increases in IL-10 mRNA and its serum protein levels elicited by the ischemia/reperfusion. Previous studies have demonstrated that neuropeptides such as CGRP [33][34][35] and somatostatin [36] inhibited the LPS-induced TNF-α production in vivo and in vitro. We also found recently that orally administered SA13353 evoked the release of CGRP and somatostatin [22].…”
Section: Discussionmentioning
confidence: 99%
“…Substance P is known to be a potent vasodilator, increasing vascular permeability and stimulating many pro-inflammatory processes, including LPS-induced TNF-α production and release [ 49 , 50 ]. Calcitonin gene-related peptide and somatostatin, on the other hand, inhibit TNF-α [ 51 - 53 ]. In our in vivo study, the RTX-treated animals reacted towards a stronger TNF-α response to systemic LPS stimulation.…”
Section: Discussionmentioning
confidence: 99%